Antioxidant Potential, Subacute Toxicity, and Beneficiary Effects of Methanolic Extract of Pomelo (Citrus grandis L. Osbeck) in Long Evan Rats - Md. Yousuf Ali; Nur-E Noushin Rumpa; Sudip Paul; Md. Sakib Hossen; E. M. Tanvir; Tareq Hossan; Moumoni Saha; Nadia Alam; Nurul Karim; Md. Ibrahim Khalil; Siew Hua Gan (Journal of Toxicology)
The aim of this study was to investigate the antioxidant potentials, subacute toxicity, and beneficiary effects of methanolic extract of pomelo (Citrus grandis L. Osbeck) in rats. Long Evans rats were divided into four groups of eight animals each. The rats were orally treated with three doses of pomelo (250, 500, and 1000 mg/kg) once daily for 21 days. Pomelo extract contained high concentrations of polyphenols, flavonoids, and ascorbic acid while exhibiting high 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity and ferric reducing antioxidant power values. There was no significant change in the body weight, percentage water content, and relative organ weight at any administered doses. In addition, no significant alterations in the hematological parameters were also observed. However, rats which received 1000 mg/kg dose had a significant reduction in some serum parameters, including alanine transaminase (15.29%), alkaline phosphatase (2.5%), lactate dehydrogenase (15.5%), γ-glutamyltransferase (20%), creatinine (14.47%), urea (18.50%), uric acid (27.14%), total cholesterol (5.78%), triglyceride (21.44%), low-density lipoprotein cholesterol (40.74%), glucose (2.48%), and all atherogenic indices including cardiac risk ratio (24.30%), Castelli’s risk index-2 (45.71%), atherogenic coefficient (42%), and atherogenic index of plasma (25%) compared to control. In addition, the highest dose (1000 mg/kg) caused a significant increase in iron (12.07%) and high-density lipoprotein cholesterol (8.87%) levels. Histopathological findings of the vital organs did not indicate any pathological changes indicating that pomelo is nontoxic, safe, and serves as an important source of natural antioxidants. In addition, the fruit extract has the potential to ameliorate hepato- and nephrotoxicities and cardiovascular diseases as well as iron deficiency anemia.